The formation of a crater on the surface of the cathode in the explosion of micro tip; Journal of Physics: Conference Series; Vol. 774 : XXXI International Conference on Equations of State for Matter (ELBRUS 2016) - Oreshkin E. V. Evgeny Vladimirovich; Barengolts S. A. Sergey Aleksandrovich; Mesyats G. A. Gennady Andreyevich; Oreshkin V. I. Vladimir Ivanovich; Khishchenko K. V. (2016, 2016)
Title screen